Polarization, risk and welfare in general equilibrium - Jørgen Heibø Modalsli (University of Oslo, Department of Economics, 2011)
This paper studies the determinants of inequality in an infnitehorizon general equilibrium model. Missing capital markets decreases motivations for capital accumulation among the poor, while uncertainty about future income leads to precautionary savings. The different returns to saving faced by agents with different levels of wealth, caused by missing capital markets, lead to two-peaked wealth distributions and high inequality. The precautionary savings, affected by the level of labor market risk, infuences the degree of polarization in the wealth distribution, as poor agents in particular save more if the income process is more volatile. With low risk, there are two distinct population groups: the poor and the rich. There is no mobility between groups, and the wealth distribution is history dependent. With high risk, there is mobility between groups and a unique steady state wealth distribution. When comparing steady states with high and low risk, the wage level is higher in the high-risk steady states because of precautionary saving. The wage may in fact be so much higher that the poor are better off in the high-risk steady states, even though the income process is more volatile. The rich are worse off with high risk, as the price paid for labor is higher.
Keywords: O15; E21; D52; 330; Inequality; polarization; income risk; credit markets; saving; Vermögensverteilung; Allgemeines Gleichgewicht; Sparen; Steady-State-Ökonomie; Unvollkommener Markt; Theorie